ANALYSIS RISK MANAGEMENT FOR PROCUREMENT OF GOODS AND SERVICES IN DAM PROJECTS - Bambang Asmoro; Silia Yuslim; Endah Kurniyaningrum (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Dam projects are construction projects with a high level of complexity and uncertainty, particularly during the procurement of goods and services. A poorly managed procurement process has the potential to pose significant risks to project performance in terms of cost, time, quality, and safety. This study aims to identify risk indicators for procurement of goods and services during the vendor selection stage of a dam project, determine priority risks based on the Severity Index (SI) and Risk Index (RI), and formulate appropriate risk responses. The research method used is a quantitative approach with data collection through literature studies, observations, interviews, and questionnaires distributed to respondents experienced in the field of procurement and dam project management. Risk analysis was conducted referring to the ISO 31000:2018 risk management framework. The results show that procurement risks are spread across aspects of administration and compliance, vendor technical and capability, financial and price, time and performance, occupational safety and health, and the supply chain. Some risks are categorized as high to very high and require priority control. This study provides a practical contribution in the form of risk mapping and risk response recommendations that can be used as a basis for procurement decisions in dam projects.